Phytochemical constituents from corn silk and antimicrobial activity of the isolates - James Oppong-kyekyeku; Isaac Ayensu; Nestor Tordzagla (International Journal of Secondary Metabolite)
Corn silk (Stigma maydis) is one of the traditional medicines for treating many microbial infections. However, there is little literature on the bioactive compounds responsible for these activities. This study was designed to investigate the phytochemical constituents present in corn silk and to screen the isolated compounds for antimicrobial activity. The pulverized plant sample of 1.14 kg was extracted with 3.6 L of methanol by cold maceration for 3 days. The extract was screened for phytochemicals, followed by isolation of constituent phytochemicals, characterization, and identification of isolated compounds. The isolates were screened for antibacterial and antifungal activities. The phytochemical screening revealed the presence of alkaloids, flavonoids, coumarins, tannins, reducing sugars, saponins, terpenoids, sterols, and cardiac glycosides. Further phytochemical investigation of the chloroformic subfraction of the methanolic extract of the silk led to the isolation of behenic acid and stigmasterol after running column chromatography as well as other chromatographic methods. The identity of the isolated compounds was established based on extensive spectroscopic analyses of their IR, 1D, 2D NMR data and comparing the data to the reported literature. Stigmasterol was active against Staphylococcus aureus and the fungal strain Candida albicans at 25 µg/mL while the mean minimum inhibitory concentration of behenic acid against Staphylococcus aureus was 100 µg/mL, Tinea corporis and Klebsiella pneumoniae were susceptible at 25 µg/mL. The study showed that plant secondary metabolites might be responsible for the reported biological activities of corn silk. It is the first report of behenic acid isolated from corn silk.